ANALISIS STRUKTUR PEREKONOMIAAN DAERAH BERDASARKAN PENDEKATAN SHIFT SHARE DI KABUPATEN SANGGAU TAHUN 2003-2011 - B01108048, AULIA RIDHA ZULFIQAR (Jurnal Pembangunan dan Pemerataan, 2014)
To know the structure of the economy in Sanggau Regency needed a useful method for assessing and projecting economic growth of the region. To then be used as a guide to determine what actions should be taken to accelerate the growth rate of existing. To answer the problem, then use a data analysis method, namely the Shift Share analysis is used to determine the structure of the regional regency economy Sanggau. Data used are secondary data from the value of Gross Domestic Product (GDP) western Kalimantan Province and Sanggau Regency at constant prices of the year 2003-2011. The results of research based on Shift Share analysis indicates that no change in the economic structure Sanggau Regency. This is indicated by the role of the primary sector through the contribution to GDP Sanggau Regency, followed by the secondary sector and the tertiary sector. Despite slow growth in the primary sector, but its contribution to GDP Sanggau Regency is very dominant. Keywords: Structure of Economy, GDP, Shift Share